A flexible perovskite thin film solar cell and a preparation method thereof
Patent Information
- Application Number
- CN202311595888.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-27
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-27
AI Technical Summary
然而,P1激光划线过程中产生的“火山口”效应会影响后续的钙钛矿太阳能电池组件的制备,增加处理“火山口”的成本,影响太阳能电池组件效率
[0033] This application provides a method for fabricating a flexible perovskite thin-film solar cell, comprising: fabricating a bottom electrode layer on the upper surface of an ultraviolet-resistant flexible substrate, and performing P1 laser scribing on the bottom electrode layer; fabricating a first transport layer on the upper surface of the bottom electrode layer; fabricating a perovskite layer on the upper surface of the first transport layer; fabricating a second transport layer on the upper surface of the perovskite layer, and performing P2 laser scribing on the first transport layer, the perovskite layer, and the second transport layer; fabricating a top electrode layer on the upper surface of the second transport layer, and performing P3 laser scribing on the top electrode layer; wherein the ultraviolet transmittance of the flexible substrate is ≤1%. In the fabrication method of the flexible perovskite thin-film solar cell provided in this application, by using an ultraviolet-resistant flexible substrate material with an ultraviolet transmittance of ≤1%, most of the laser energy transmitted through the bottom electrode layer and irradiating the ultraviolet-resistant flexible substrate is absorbed, rapidly generating a large amount of heat. This makes the etching and removal of the bottom electrode layer material more rapid, resulting in cleaner material removal, smoother trench sides, and reduced ridge height on both sides of the trench. This significantly reduces the "crater" effect generated during the P1 laser scribing process, improving the efficiency of the solar cell module while reducing the need for "crater" treatment, effectively lowering the cost of module fabrication. This application also provides a flexible perovskite thin-film solar cell with high photoelectric conversion efficiency.
Smart Images

Figure CN117396009B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solar cell technology, and in particular to a flexible perovskite thin-film solar cell and its preparation method. Background Technology
[0002] Perovskite thin-film solar cells are a type of solar cell that uses perovskite-type organometal halide semiconductors as light-absorbing materials. As a novel type of solar cell, they have the advantages of high photoelectric conversion efficiency and low production cost.
[0003] Laser scribing is widely used in the production of thin-film solar cell modules. The production of perovskite thin-film solar cell modules requires three laser scribing processes (P1, P2, and P3) to establish a series connection structure between multiple individual cells, enabling the solar cells to achieve a high open-circuit voltage. Specifically, P1 scribing involves using a laser to scribble lines through the transparent conductive oxide (TCO) layer without damaging the substrate. However, the "crater" effect generated during P1 laser scribing can affect the subsequent fabrication of perovskite solar cell modules, increasing the cost of handling the "crater" and impacting the efficiency of the solar cell modules. Summary of the Invention
[0004] The purpose of this application is to provide a flexible perovskite thin-film solar cell and its fabrication method, so as to reduce the "crater effect" generated during the P1 laser scribing process and improve the efficiency of the solar cell module. The specific technical solution is as follows:
[0005] The first aspect of this application provides a method for fabricating a flexible perovskite thin-film solar cell, comprising:
[0006] A bottom electrode layer is prepared on the upper surface of an anti-ultraviolet flexible substrate, and the bottom electrode layer is scribed with a P1 laser.
[0007] A first transport layer is prepared on the upper surface of the bottom electrode layer;
[0008] A perovskite layer is prepared on the upper surface of the first transport layer;
[0009] A second transport layer is prepared on the upper surface of the perovskite layer, and P2 laser scribing is performed on the first transport layer, the perovskite layer, and the second transport layer.
[0010] A top electrode layer is prepared on the upper surface of the second transport layer, and the top electrode layer is scribed with a P3 laser.
[0011] The ultraviolet transmittance of the flexible substrate is ≤1%.
[0012] In some embodiments, the UV-resistant flexible substrate material is selected from at least one of polyethylene terephthalate (PET), polyetherimide (PEI), polyimide (PI), and polyethylene naphthalate (PEN).
[0013] The bottom electrode layer material is selected from at least one of indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium zinc oxide (IZO), indium gallium oxide (IGO), aluminum-doped zinc oxide (AZO), or tungsten-doped indium oxide (IWO);
[0014] The first transport layer material is selected from polytriarylamine, polyethylene dioxythiophene-polystyrene sulfonate, and NiO. x SnO z At least one of TiO2, ZnO, ZnTiO3, tungsten trioxide (WO3) or C60 and its derivatives;
[0015] The precursor material for the perovskite layer includes A. p (CH4N2) y (CH3NH2) q B(I 1-n Br n 3. A is selected from Cs, K or Rb, B is selected from Pb, Sn, Ti or Zr, 0≤p≤1, 0≤y≤1, 0≤q≤1, and p+y+q=1, 0≤n≤1;
[0016] The second transport layer material is selected from copper phthalocyanine, polytriarylamine, poly(3-hexylthiophene-2,5-diyl), spirodifluorene hole transport materials, and SnO. z NiO x At least one of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Sprio-OMeTAD), TiO2, ZnO, ZnTiO3, WO3 or C60 and their derivatives;
[0017] The top electrode layer material is selected from at least one of ITO, FTO, IZO, IGO, AZO, IWO, Cu, Al, Ag or Au.
[0018] In some embodiments, the P1 laser scribing includes:
[0019] The laser emitted by the laser is used to draw lines. The incident direction of the laser is to pass through the bottom electrode layer and then through the UV-resistant flexible substrate. The incident direction of the laser is perpendicular to the plane of the bottom electrode layer.
[0020] The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ.
[0021] The distance d between the focal point formed by the laser beam of the laser after passing through the focusing lens and the bottom electrode layer is 0-1mm.
[0022] In some embodiments, the bottom electrode layer is prepared by physical vapor deposition; the first transport layer is prepared by coating, physical vapor deposition, chemical vapor deposition, or atomic layer deposition; the perovskite layer is prepared by slot coating or physical vapor deposition; the second transport layer is prepared by coating, physical vapor deposition, chemical vapor deposition, or atomic layer deposition; and the top electrode layer is prepared by physical vapor deposition.
[0023] In some embodiments, the thickness of the UV-resistant flexible substrate is 150-250 μm; the thickness of the bottom electrode layer is 50-70 nm; the thickness of the first transport layer is 20-200 nm; the thickness of the perovskite layer is 400-800 nm; the thickness of the second transport layer is 20-200 nm; and the thickness of the top electrode layer is 100-500 nm.
[0024] In some implementations, the P2 line includes:
[0025] The laser emitted by the laser is used to draw lines. The incident direction of the laser passes through the second transmission layer, the perovskite layer and the first transmission layer in sequence. The incident direction of the laser is perpendicular to the plane of the second transmission layer.
[0026] The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ.
[0027] The distance between the focal point formed by the laser beam of the laser after passing through the focusing lens and the second transmission layer is 0-1mm.
[0028] In some implementations, the P3 line includes:
[0029] The laser emitted by the laser is used to draw lines, and the incident direction of the laser is through the top electrode layer and perpendicular to the plane of the top electrode layer.
[0030] The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ.
[0031] The distance between the focal point formed by the laser beam of the laser after passing through the focusing lens and the top electrode layer is 0-1 mm.
[0032] The second aspect of this application provides a flexible perovskite thin-film solar cell prepared according to the preparation method provided in the first aspect of this application.
[0033] This application provides a method for fabricating a flexible perovskite thin-film solar cell, comprising: fabricating a bottom electrode layer on the upper surface of an ultraviolet-resistant flexible substrate, and performing P1 laser scribing on the bottom electrode layer; fabricating a first transport layer on the upper surface of the bottom electrode layer; fabricating a perovskite layer on the upper surface of the first transport layer; fabricating a second transport layer on the upper surface of the perovskite layer, and performing P2 laser scribing on the first transport layer, the perovskite layer, and the second transport layer; fabricating a top electrode layer on the upper surface of the second transport layer, and performing P3 laser scribing on the top electrode layer; wherein the ultraviolet transmittance of the flexible substrate is ≤1%. In the fabrication method of the flexible perovskite thin-film solar cell provided in this application, by using an ultraviolet-resistant flexible substrate material with an ultraviolet transmittance of ≤1%, most of the laser energy transmitted through the bottom electrode layer and irradiating the ultraviolet-resistant flexible substrate is absorbed, rapidly generating a large amount of heat. This makes the etching and removal of the bottom electrode layer material more rapid, resulting in cleaner material removal, smoother trench sides, and reduced ridge height on both sides of the trench. This significantly reduces the "crater" effect generated during the P1 laser scribing process, improving the efficiency of the solar cell module while reducing the need for "crater" treatment, effectively lowering the cost of module fabrication. This application also provides a flexible perovskite thin-film solar cell with high photoelectric conversion efficiency. Attached Figure Description
[0034] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these drawings.
[0035] Figure 1 This is a schematic diagram of P1 laser scribing performed on the structural assembly including the UV-resistant flexible substrate and the bottom electrode layer in Example 1;
[0036] Figure 2This is a photograph of the surface morphology of the bottom electrode layer during the P1 laser scribing process in Example 1;
[0037] Figure 3 This is a schematic diagram of the unit structure of the flexible perovskite thin-film solar cell in Example 1;
[0038] Figure 4 This is a schematic diagram of P1 laser scribing performed on the structural assembly including the substrate and bottom electrode layer in Comparative Example 1.
[0039] Figure 5 This is a photograph of the surface morphology of the bottom electrode layer during laser scribing in Comparative Example 1;
[0040] Among them, 101. UV-resistant flexible substrate, 120. bottom electrode layer, 121. trench, 130. first transport layer, 140. perovskite layer, 150. second transport layer, 160. top electrode layer; 100. substrate, 122. "crater". Detailed Implementation
[0041] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0042] The first aspect of this application provides a method for fabricating a flexible perovskite thin-film solar cell, comprising:
[0043] A bottom electrode layer is prepared on the upper surface of an anti-ultraviolet flexible substrate, and the bottom electrode layer is scribed with a P1 laser.
[0044] A first transport layer is prepared on the upper surface of the bottom electrode layer;
[0045] A perovskite layer is prepared on the upper surface of the first transport layer;
[0046] A second transport layer is prepared on the surface of the perovskite layer, and P2 laser scribing is performed on the first transport layer, the perovskite layer, and the second transport layer.
[0047] A top electrode layer is prepared on the upper surface of the second transport layer, and the top electrode layer is scribed with a P3 laser.
[0048] The ultraviolet transmittance of the flexible substrate is ≤1%.
[0049] During the P1 laser scribing process, the materials of the substrate and the bottom electrode layer heat up and expand after absorbing the laser energy. A huge stress difference is generated at the interface of the materials, which causes the bottom electrode layer on the substrate to be etched away. However, since the laser is a Gaussian beam, the laser energy is weaker at the edge of the laser spot. On the one hand, the material at the edge of the spot cannot absorb enough heat to cause the bottom electrode layer material to fall off, thus leaving a high ridge at the edge of the etched trench. On the other hand, when the laser power is increased to increase the laser energy at the edge of the spot, the substrate material inside the spot and at the edge of the spot will undergo a large degree of deformation. In the method for fabricating flexible perovskite thin-film solar cells provided in this application, by using an ultraviolet-resistant flexible substrate material with an ultraviolet transmittance of ≤1%, most of the laser energy transmitted through the bottom electrode layer and irradiating the ultraviolet-resistant flexible substrate is absorbed, rapidly generating a large amount of heat. This makes the etching and removal of the bottom electrode layer material faster, resulting in cleaner etching and removal of the bottom electrode layer material, smoother trench sides, and reduced height of the ridges on both sides of the trench. This significantly reduces the "crater" effect generated during the P1 laser scribing process, improving the efficiency of the solar cell module while reducing the processing steps for the "crater," effectively lowering the cost of module fabrication.
[0050] In some implementations, the height of the "crater" on both sides of the trench etched on the bottom electrode layer after P1 laser scribing is less than 25 nm.
[0051] The P1 laser scribing described in this application can be performed by fixing a structural assembly including an anti-ultraviolet flexible substrate and a bottom electrode layer on the stage of a laser scribing device after the bottom electrode layer is prepared, so that the laser passes through the bottom electrode layer and the anti-ultraviolet flexible substrate layer in sequence to scribing grooves in the bottom electrode layer.
[0052] The inventors discovered that by using the UV-resistant flexible substrate with a UV transmittance close to 0 as described in this application, the UV-resistant flexible substrate material can absorb most of the laser energy. After being scribed with a P1 laser, the bottom electrode layer material is easily detached, resulting in a smooth and clean edge of the groove etched by the bottom electrode layer. This greatly reduces the "crater" lifting at the edge of the groove, allowing the "crater" height to be reduced to below 20nm. This helps reduce the labor and time costs of handling the "crater," lowers the manufacturing cost of solar cells, and improves the efficiency of solar cell modules.
[0053] In some embodiments, the UV-resistant flexible substrate material is selected from at least one of PET, PEI, PI, and PEN;
[0054] The bottom electrode layer material is selected from at least one of ITO, FTO, IZO, IGO, AZO or IWO;
[0055] The first transport layer material is selected from polytriarylamine, polyethylene dioxythiophene-polystyrene sulfonate, and NiO. x SnO z At least one of TiO2, ZnO, ZnTiO3, WO3 or C60 and their derivatives;
[0056] The precursor material for the perovskite layer includes A. p (CH4N2) y (CH3NH2) q B(I 1-n Br n 3. A is selected from Cs, K or Rb, B is selected from Pb, Sn, Ti or Zr, 0≤p≤1, 0≤y≤1, 0≤q≤1, and p+y+q=1, 0≤n≤1;
[0057] The second transport layer material is selected from copper phthalocyanine, polytriarylamine, poly(3-hexylthiophene-2,5-diyl), spirodifluorene hole transport materials, and SnO. z NiO x At least one of Sprio-OMeTAD, TiO2, ZnO, ZnTiO3, WO3 or C60 and their derivatives (such as fullerenes (PCBM));
[0058] The top electrode layer material is selected from at least one of ITO, FTO, IZO, IGO, AZO, IWO, Cu, Al, Ag or Au.
[0059] By selecting the aforementioned first transport layer material, this application improves the carrier migration performance of the first transport layer; by selecting the aforementioned perovskite layer precursor material, it improves the photoelectric conversion efficiency of the flexible perovskite thin-film solar cell; by selecting the aforementioned second transport layer material, it improves the carrier migration performance of the second transport layer; by selecting the aforementioned top electrode layer material, it improves the conductivity of the top electrode layer; and the flexible perovskite thin-film solar cell prepared by selecting the aforementioned layer materials has good photoelectric conversion efficiency.
[0060] In this application, exemplarily, the NiO x Including but not limited to NiO, the SnO z Including but not limited to SnO2.
[0061] In some embodiments, the P1 laser scribing includes:
[0062] The laser emitted by the laser is used to draw lines. The incident direction of the laser is to pass through the bottom electrode layer and then through the UV-resistant flexible substrate. The incident direction of the laser is perpendicular to the plane of the bottom electrode layer.
[0063] The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ.
[0064] The distance d between the focal point formed by the laser beam of the laser after passing through the focusing lens and the bottom electrode layer is 0-1mm.
[0065] This application does not specifically limit the laser used, as long as it can achieve the purpose of this application; preferably, the laser is a solid-state laser or a gas laser; the inventors have discovered that using a solid-state laser or a gas laser for laser scribing can achieve high laser scribing accuracy, smooth scribing cuts, and fast etching speed. For example, the laser is a neodymium-doped yttrium aluminum garnet (Nd:YAG) laser.
[0066] The inventors have discovered that when the wavelength, average power, spot diameter, pulse width, pulse energy, and the distance between the focal point formed by the laser beam after passing through the focusing lens and the bottom electrode layer are adjusted within the range of this application, smooth grooves can be etched in the bottom electrode layer while avoiding laser damage to the substrate material. The inventors have also discovered that by setting the spacing between adjacent laser spots to achieve an overlap rate of 40-80%, continuous etched grooves can be obtained; preferably, the spacing between adjacent laser spots is 5-10 μm.
[0067] In some embodiments, the bottom electrode layer is prepared by physical vapor deposition; the first transport layer is prepared by coating, physical vapor deposition, chemical vapor deposition, or atomic layer deposition; the perovskite layer is prepared by slot coating or physical vapor deposition; the second transport layer is prepared by coating, physical vapor deposition, chemical vapor deposition, or atomic layer deposition; and the top electrode layer is prepared by physical vapor deposition.
[0068] In this application, the physical vapor deposition can be selected from thermal evaporation, magnetron sputtering, or ion plating (Plasma Gun).
[0069] In this application, there is no particular limitation on the thickness of each layer of the flexible perovskite thin-film solar cell, as long as the purpose of this application can be achieved; in some embodiments, the thickness of the UV-resistant flexible substrate is 150-250 μm; the thickness of the bottom electrode layer is 50-70 nm; the thickness of the first transport layer is 20-200 nm; the thickness of the perovskite layer is 400-800 nm; the thickness of the second transport layer is 20-200 nm; and the thickness of the top electrode layer is 100-500 nm.
[0070] In some implementations, the P2 line includes:
[0071] The laser emitted by the laser is used to draw lines. The incident direction of the laser passes through the second transmission layer, the perovskite layer and the first transmission layer in sequence. The incident direction of the laser is perpendicular to the plane of the second transmission layer.
[0072] The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ.
[0073] The distance between the focal point formed by the laser beam of the laser after passing through the focusing lens and the second transmission layer is 0-1mm.
[0074] In this application, the P2 scribing is for etching each functional layer without damaging the bottom electrode layer.
[0075] In some implementations, the P3 line includes:
[0076] The laser emitted by the laser is used to draw lines, and the incident direction of the laser is through the top electrode layer and perpendicular to the plane of the top electrode layer.
[0077] The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ.
[0078] The distance between the focal point formed by the laser beam of the laser after passing through the focusing lens and the top electrode layer is 0-1 mm.
[0079] In this application, the P3 scribing is for etching the top electrode layer without damaging other functional layers.
[0080] This application employs an ultraviolet-resistant flexible substrate material with an ultraviolet transmittance of ≤1% for laser light. This allows most of the laser energy transmitted through the bottom electrode layer and irradiating the flexible substrate to be absorbed, rapidly generating a large amount of heat. This makes the etching and removal of the bottom electrode layer material faster, resulting in cleaner material removal, smoother trench sides, and reduced ridge height on both sides of the trench. This significantly reduces the "crater" effect generated during the P1 laser scribing process, improving the efficiency of the solar cell module while reducing the need for "crater" treatment, effectively lowering the manufacturing cost of the solar cell.
[0081] The second aspect of this application provides a flexible perovskite thin-film solar cell fabricated according to the preparation method provided in the first aspect of this application. The flexible perovskite thin-film solar cell provided by this application has good photoelectric conversion efficiency.
[0082] Example
[0083] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0084] Test methods and equipment:
[0085] UV transmittance test:
[0086] A UV-Vis spectrophotometer (Shimadzu, Japan, model: UV-1800) was used, with the measurement mode set to transmittance (%T), the measurement wavelength range set to 190-400 nm, and the wavelength scan speed set to slow. The UV transmittance of the sample was measured.
[0087] Measurement of the height of the crater:
[0088] Using a laser confocal microscope (manufacturer: Olympus, model: OLS5100), adjust the microscope height to focus on the surface of the sample to be tested, click the "Start 3D Acquisition" button, open the acquired image, set the measurement item to "Height", and measure the height of the "crater" at the test location.
[0089] Open-circuit voltage and photoelectric conversion efficiency testing of solar cells:
[0090] Using a solar simulator (Newport Oriel, USA) and a digital source meter (Keithley 2420, USA), and Oriel 2.0 software, the voltage range was set to -0.1 to 1.2V, and the effective cell area was 0.1 cm². 2 Scanning direction: reverse scan; scan rate: 10mV / s; the open-circuit voltage and photoelectric conversion efficiency of flexible perovskite thin-film solar cells were measured.
[0091] Example 1
[0092] <Preparation of the bottom electrode layer>
[0093] A 200μm thick, UV-resistant flexible substrate (PET with 1% UV transmittance, manufactured by Jiangsu Yuxing Thin Film Technology Co., Ltd., model: CY25HT(GU)) was used as the substrate. A 60nm thick ITO film was deposited on the surface of the substrate using magnetron sputtering to obtain the bottom electrode layer. The structural assembly, including the UV-resistant flexible substrate and the bottom electrode layer, was fixed on the stage of a laser scribing device. A Nd:YAG (neodymium-doped yttrium aluminum garnet) laser (manufacturer: Edgewave, Germany, model: PX200-3-GF) was used to scribing the bottom electrode layer with P1 laser lines, resulting in smooth grooves. The bottom electrode layer was used to measure the height of the "crater" at 20 nm. In the P1 laser scribing process, the laser's incident direction passed through the bottom electrode layer first and then through the UV-resistant flexible substrate. The laser's incident direction was perpendicular to the plane of the bottom electrode layer. The laser wavelength was 355 nm, the average laser power was 10 W, the laser spot diameter was 10 μm, the spacing between adjacent spots was 7 μm for scribe grooves, the laser pulse width was 12 ps, the laser pulse energy was 8 μJ, and the distance between the focal point of the laser beam after passing through the focusing lens and the bottom electrode layer was 0.5 mm. A schematic diagram of the P1 laser scribing process, including the UV-resistant flexible substrate and the bottom electrode layer, is shown below. Figure 1 As shown, the surface morphology of the bottom electrode layer was photographed during laser scribing in P1 (laser confocal microscope, manufacturer: Olympus, model: OLS5100). Figure 2 As shown, the grooves after laser scribing by P1 consist of a series of... Figure 2 The pit shown in the figure has a diameter of 12 μm.
[0094] <Preparation of the First Transport Layer>
[0095] The NiO target was installed in the magnetron sputtering coating equipment. The device with P1 scribing was placed in the magnetron sputtering vacuum chamber. Then, by adjusting the sputtering power to 500W, the sputtering atmosphere and flow rate to Ar:O2 = 300:50 (sccm), and the sputtering time to 25min, a first transport layer with a thickness of 20nm was obtained.
[0096] <Preparation of Perovskite Layer>
[0097] 44 mL of hydroiodic acid (48%) was added to 27.8 mL of methylamine aqueous solution (40%), and stirred at 0 °C for 2 h in an ice bath. The product was evaporated at 50 °C for 1 h, the precipitate was dissolved in anhydrous ethanol, recrystallized in diethyl ether, and finally dried at 60 °C for 24 h under vacuum to obtain CH3NH2I. CH3NH2I and PbI2 were added to dimethylformamide in a 1:1 molar ratio and reacted at 60 °C for 12 h to obtain 1.0 mol / L CH3NH2PbI3. CH3NH2PbI3 was slit-coated onto the upper surface of the first transport layer to a thickness of 5 μm and dried at 100 °C for 5 min to crystallize into a film, resulting in a perovskite layer with a thickness of 500 nm.
[0098] <Preparation of the Second Transport Layer>
[0099] Solid PCBM was dissolved in chlorobenzene at a concentration of 20 mg / mL. The PCBM solution was slit-coated onto the surface of the perovskite layer and then dried in a 150°C oven for 30 min to form a second transport layer with a thickness of 100 nm. The layer was then fixed on the stage of a laser scribing device, and a Nd:YAG laser was used to perform P2 laser scribing on the second transport layer, the perovskite layer, and the first transport layer to obtain a second transport layer, the perovskite layer, and the first transport layer with smooth grooves. In the P2 laser scribing, the incident direction of the laser passed through the second transport layer, the perovskite layer, and the first transport layer in sequence. The incident direction of the laser was perpendicular to the plane of the second transport layer. The laser wavelength was 355 nm, the average power of the laser was 10 W, the laser spot diameter was 10 μm, the laser pulse width was 12 ps, the laser pulse energy was 8 μJ, and the distance between the focal point of the laser beam formed by the focusing lens and the second transport layer was 0.5 mm.
[0100] <Preparation of the Top Electrode Layer>
[0101] A 200nm thick layer of ITO material is deposited on the upper surface of the second transmission layer by thermal evaporation to obtain the top electrode layer. Then, it is fixed on the stage of a laser scribing device, and a neodymium-doped yttrium aluminum garnet (Nd:YAG) laser is used to perform P3 laser scribing on the top electrode layer to obtain a top electrode layer with smooth grooves. In the P3 laser scribing, the incident direction of the laser is through the top electrode layer and perpendicular to the plane of the top electrode layer. The laser wavelength is 355nm, the average power of the laser is 10W, the laser spot diameter is 10μm, the laser pulse width is 12ps, the laser pulse energy is 8μJ, and the distance between the focal point of the laser beam formed by the focusing lens and the top electrode layer is 0.5mm.
[0102] A flexible perovskite thin-film solar cell was obtained, and its unit structure schematic diagram is shown below. Figure 3 As shown.
[0103] Examples 2-5
[0104] Except for adjusting the P1 laser scribing conditions as shown in Table 1 in the <Preparation of Bottom Electrode Layer>, the rest is the same as in Example 1.
[0105] Example 6
[0106] <Preparation of the bottom electrode layer>
[0107] Except for replacing the UV-resistant flexible substrate PET with PI (manufacturer: Yingkou Opivet New Energy Technology Co., Ltd., model: OPV-PI-50) and replacing the ITO film with the AZO film, the rest is the same as in Example 1.
[0108] <Preparation of the First Transport Layer>
[0109] Polyethylene dioxythiophene-polystyrene sulfonate was dispersed in water. After 5 wt% of the polyethylene dioxythiophene-polystyrene sulfonate precursor solution was slit-coated on the upper surface of the bottom electrode layer, it was then placed in a drying oven at 150°C for 30 min to form a film, resulting in a first transport layer with a thickness of 50 nm.
[0110] <Preparation of Perovskite Layer>
[0111] Dissolve CsI (final concentration 21.4 mg / mL), CH3NH2Br (final concentration 11.9 mg / mL), CH4N2I (final concentration 210.4 mg / mL), PbI2 (final concentration 589.5 mg / mL), and PbBr2 (final concentration 56.4 mg / mL) in a mixed solution of DMF and DMSO (8:1 v / v) to prepare CsI solution. 0.05 ((CH4N2) 0.92 (CH3NH2) 0.08 ) 0.95 Pb(I 0.92 Br 0.08 )3. Precursor solution; The precursor solution was slit-coated on the upper surface of the first transport layer with a thickness of 5 μm, and dried at 100 °C for 30 min to crystallize into a film, resulting in a perovskite layer with a thickness of 500 nm.
[0112] <Preparation of the Second Transport Layer>
[0113] A polytriarylamine-chlorobenzene solution (20 mg / mL) was slit-coated onto the surface of the perovskite layer, and then dried in a drying oven at 150°C for 30 min to form a film, resulting in a second transport layer with a thickness of 100 nm. The film was then fixed on the stage of a laser scribing device, and a Nd:YAG (neodymium-doped yttrium aluminum garnet) laser was used to perform P2 laser scribing on the second transport layer, the perovskite layer, and the first transport layer, resulting in a second transport layer, the perovskite layer, and the first transport layer with smooth grooves. The parameters in the P2 laser scribing were the same as in Example 1.
[0114] <Preparation of the Top Electrode Layer>
[0115] A 200 nm thick Al layer is deposited on the upper surface of the second transmission layer by thermal evaporation to obtain the top electrode layer; then it is fixed on the stage of a laser scribing device, and a Nd:YAG (neodymium-doped yttrium aluminum garnet) laser is used to perform P3 laser scribing on the top electrode layer to obtain a top electrode layer with smooth grooves; wherein, the parameters in the P3 laser scribing are the same as in Example 1;
[0116] Flexible perovskite thin-film solar cells were obtained.
[0117] Comparative Example 1
[0118] Except for replacing the PET with a UV transmittance of 1% on the UV-resistant flexible substrate with a PET with a UV transmittance of 25% (manufacturer: Jiangsu Yuxing Thin Film Technology Co., Ltd., model: CY25HT(G48)), everything else is the same as in Example 1. A schematic diagram of the P1 laser scribing of the structural components, including the substrate and the bottom electrode layer, is shown below. Figure 4 As shown, the surface morphology of the bottom electrode layer is photographed during P1 laser scribing, as follows: Figure 5 As shown, the grooves after laser scribing by P1 consist of a series of... Figure 5 The pit shown in the figure has a diameter of 10 μm.
[0119] Comparative Example 2
[0120] Except for replacing the PET with a UV transmittance of 1% on the UV-resistant flexible substrate with PET with a UV transmittance of 85% (manufacturer: Jiangsu Yuxing Film Technology Co., Ltd., model: 6027D), the rest is the same as in Example 1.
[0121]
[0122] As shown in Table 1, according to Examples 1-6 and Comparative Examples 1-2, this application uses an UV-resistant flexible substrate material with an ultraviolet transmittance of ≤1%. This allows most of the laser energy transmitted through the bottom electrode layer and irradiating the UV-resistant flexible substrate to be absorbed, rapidly generating a large amount of heat in the substrate. This makes the etching and removal of the bottom electrode layer material more rapid, resulting in cleaner etching and removal of the bottom electrode layer material. This significantly reduces the height of the "crater" generated during the P1 laser scribing process, giving the fabricated flexible perovskite thin-film solar cell better photoelectric conversion efficiency. In Examples 1-5, the inventors, during the preparation process... It was found that when the average power of the laser in the P1 laser scribing process is controlled within the range of 8-12W, the spot diameter within the range of 5-20μm, the pulse width within the range of 8-15ps, the pulse energy within the range of 5-10μJ, and the distance d between the focal point formed by the laser beam after passing through the focusing lens and the bottom electrode layer is within the range of 0-1mm, the grooves of the bottom electrode layer after laser scribing are smoother and cleaner, and the height of the "crater" generated during the P1 laser scribing process is less than 25nm. At the same time, it can avoid damage to the flexible substrate material against ultraviolet light caused by the laser, thereby enabling the fabricated flexible perovskite thin film solar cell to have better photoelectric conversion efficiency.
[0123] according to Figure 1-2 , Figure 4-5 It can be seen that, as Figure 2 As shown, using the preparation method of this application, the edges of the bottom electrode layer trenches are smooth and clean after P1 laser scribing, while greatly reducing the "crater" protrusion at the trench edges and significantly lowering the height of the crater; while as Figure 5 As shown, using conventional preparation methods, the edges of the trenches in the bottom electrode layer are not completely removed, resulting in a high "crater" with a height of over 100 nm.
[0124] In summary, the fabrication method of the flexible perovskite thin-film solar cell of this application can reduce the height of the "crater" on both sides of the trench etched on the bottom electrode layer after P1 laser scribing, reduce the labor and time costs of processing the "crater", and improve the cell efficiency of the flexible perovskite thin-film solar cell module.
[0125] The above description is merely a preferred embodiment of this application and is not intended to limit the scope of protection of this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A method for fabricating a flexible perovskite thin-film solar cell, comprising: A bottom electrode layer is prepared on the upper surface of an anti-ultraviolet flexible substrate, and the bottom electrode layer is scribed with a P1 laser. A first transport layer is prepared on the upper surface of the bottom electrode layer; A perovskite layer is prepared on the upper surface of the first transport layer; A second transport layer is prepared on the upper surface of the perovskite layer, and P2 laser scribing is performed on the first transport layer, the perovskite layer, and the second transport layer. A top electrode layer is prepared on the upper surface of the second transport layer, and the top electrode layer is scribed with a P3 laser. The ultraviolet transmittance of the UV-resistant flexible substrate is ≤1%. The P1 laser scribing includes: The laser emitted by the laser is used to draw lines. The incident direction of the laser is to pass through the bottom electrode layer and then through the UV-resistant flexible substrate. The incident direction of the laser is perpendicular to the plane of the bottom electrode layer. The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ. The distance d between the focal point formed by the laser beam of the laser after passing through the focusing lens and the bottom electrode layer is 0-1mm.
2. The preparation method according to claim 1, wherein, The UV-resistant flexible substrate material is selected from at least one of polyethylene terephthalate, polyetherimide, polyimide, and polyethylene naphthalate; The bottom electrode layer material is selected from at least one of ITO, FTO, IZO, IGO, AZO or IWO; The first transport layer material is selected from polytriarylamine, polyethylene dioxythiophene-polystyrene sulfonate, and NiO. x SnO z At least one of TiO2, ZnO, ZnTiO3, WO3 or C60 and their derivatives; The precursor material for the perovskite layer includes A. p (CH4N2) y (CH3NH2) q B(I 1-n Br n 3. A is selected from Cs, K or Rb, B is selected from Pb, Sn, Ti or Zr, 0≤p≤1, 0≤y≤1, 0≤q≤1, and p+y+q=1, 0≤n≤1; The second transport layer material is selected from copper phthalocyanine, polytriarylamine, poly(3-hexylthiophene-2,5-diyl), and SnO. z NiO x Spiro-OMeTAD, TiO2, ZnO, ZnTiO3, WO3 or C60 and their derivatives; The top electrode layer material is selected from at least one of ITO, FTO, IZO, IGO, AZO, IWO, Cu, Al, Ag or Au.
3. The preparation method according to claim 1, wherein, The bottom electrode layer is prepared by physical vapor deposition; the first transport layer is prepared by coating, physical vapor deposition, chemical vapor deposition or atomic layer deposition; the perovskite layer is prepared by slot coating or physical vapor deposition; the second transport layer is prepared by coating, physical vapor deposition, chemical vapor deposition or atomic layer deposition; and the top electrode layer is prepared by physical vapor deposition.
4. The preparation method according to claim 1, wherein, The thickness of the UV-resistant flexible substrate is 150-250 μm; the thickness of the bottom electrode layer is 50-70 nm; the thickness of the first transport layer is 20-200 nm; the thickness of the perovskite layer is 400-800 nm; the thickness of the second transport layer is 20-200 nm; and the thickness of the top electrode layer is 100-500 nm.
5. The preparation method according to claim 1, wherein, The P2 laser scribing includes: The laser emitted by the laser is used to draw lines. The incident direction of the laser passes through the second transmission layer, the perovskite layer and the first transmission layer in sequence. The incident direction of the laser is perpendicular to the plane of the second transmission layer. The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ. The distance between the focal point formed by the laser beam of the laser after passing through the focusing lens and the second transmission layer is 0-1mm; The P3 laser scribing includes: The laser emitted by the laser is used to draw lines, and the incident direction of the laser is through the top electrode layer and perpendicular to the plane of the top electrode layer. The laser has a wavelength of 350-360nm; an average power of 8-12W; a spot diameter of 5-20μm; a pulse width of 8-15ps; and a pulse energy of 5-10μJ. The distance between the focal point formed by the laser beam of the laser after passing through the focusing lens and the top electrode layer is 0-1 mm.
6. A flexible perovskite thin-film solar cell prepared by the method according to any one of claims 1-5.
Citation Information
Patent Citations
Preparation method of perovskite solar cell module
CN114361350A
Perovskite solar battery which contains laminated composite transport layer, and method for preparing same
WO2021218523A1